Direct role of viral hemagglutinin in B-cell mitogenesis by influenza viruses. - Poumbourios, P (1987)
The mitogenic activity of influenza virus is a function of the hemagglutinin (HA) molecule. Purified HA is mitogenic for murine B lymphocytes but not T lymphocytes. Furthermore, like the intact virus, HA of the H2 (but not H3) subtype is mitogenic only for B cells expressing the class II major histocompatibility complex glycoprotein I-E. Since virus bearing uncleaved HA is as mitogenic as virus bearing cleaved HA, the membrane fusion activity of the HA molecule is not involved.